Pengaruh Pemasaran Relasional dan Nilai Konsumen terhadap Keputusan Pembelian Smartphone Samsung pada Suastika Jaya Cell - Oktaviani, Luh The; Hartati, Putu Sri; Abiyoga Wulandari, Ni Luh Adisti (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The formulation of the problem and objectives of this research is to determine the influence of relationship marketing and consumer values on purchasing decisions for Samsung smartphones at Suastika Jaya Cell in Tabanan. The population in this research is consumers who buy Samsung Suastika Jaya Cell Smartphones in Tabanan. The sample used in this research was 90 respondents who were determined using a purposive sampling technique. The data in this research was collected through observation, interviews, questionnaires and then tested using multiple linear regression analysis techniques. From the research results it can be seen that relationship marketing has a positive and significant effect on purchasing decisions. Consumer values have a positive and significant effect on purchasing decisions. Relationship marketing and consumer value have a positive and significant effect on purchasing decisions. The magnitude of the influence of the independent variable on purchasing decisions is 61.7%. The best advice given to Suastika Jaya Cell is that it must be able to increase consumer confidence regarding the Samsung Smartphone products being sold that are original products and that the products are still sealed and have an official guarantee from the company so that consumers will be more confident that the products being sold are original products.